Efeitos da idade na glicosilação de histonas de núcleos de neurônios corticais de camundongos - Souza, Tafarel Andrade (2015)
Several functions have been attributed to the addition of glycidyl radicals in nuclear proteins. It is believed that the structural and functional changes through which they pass along the neurons of aging are associated with different patterns of protein glycosylation in the nucleus of these cells. Previous data refer that the glycosylation of nuclear proteins, mainly histones, plays an important role in epigenetic control of nuclear functions. In this context, the changes in chromatin structure epigenetic changes associates with type O-glycosylation depend, for example, the chromatin remodeling complex recruitment necessary for regulating gene transcription, with this type of control over the aging-related rise neurodegenerative diseases such as Alzheimer s disease and others. Thus, to understand the association between changes in chromatin structure due to O-glycosylation of histones and aging is critical to the development of treatments that can improve the quality of life of the population. For this purpose, it propose to study the in situ distribution of two types of sugar residues attached to proteins, as well as histones are glycosylated and if there differential glycosylation of the proteins along with aging. To this end, isolated neuronal nuclei were underwent cytochemical analysis, and biochemical assays to identify and quantify reactive glycidiy markers to ConA and WGA lectins. Results indicate that glycoproteins containing glucose / mannose and Nacetylglucosamine have differences in their pattern of nuclear distribuition, which depend on the animal age, indicating different functions depending on the composition glicidic of these glycoproteins. Our data show that all canonical (H2A, H2B, H3 e H4) in neurons are glycosylated, with different patterns are observed for each different ages. It is believed that these changes are related to structural changes in chromatin observed during the aging period, which may have a fundamental role in altered patterns of gene expression observed with increasing age.